Australian Native Title Anthropology Strategic practice, the law and the state - Palmer, Kingsley (ANU Press, 2018)
"The Australian Federal Native Title Act 1993 marked a revolution in the recognition of the rights of Australia's Indigenous peoples. The legislation established a means whereby Indigenous Australians could make application to the Federal Court for the recognition of their rights to traditional country. The fiction that Australia was terra nullius (or 'void country'), which had prevailed since European settlement, was overturned. The ensuing legal cases, mediated resolutions and agreements made within the terms of the Native Title Act quickly proved the importance of having sound, scholarly and well-researched anthropology conducted with claimants so that the fundamentals of the claims made could be properly established. In turn, this meant that those opposing the claims would also benefit from anthropological expertise. This is a book about the practical aspects of anthropology that are relevant to the exercise of the discipline within the native title context. The engagement of anthropology with legal process, determined by federal legislation, raises significant practical as well as ethical issues that are explored in this book. It will be of interest to all involved in the native title process, including anthropologists and other researchers, lawyers and judges, as well as those who manage the claim process. It will also be relevant to all who seek to explore the role of anthropology in relation to Indigenous rights, legislation and the state."